The interplay of gender, age, education level and thermal satisfaction: Evidence from Bosnia and Herzegovina - Ljiljan Veselinović; Jasmina Mangafić (Economic Review: Journal of Economics and Business, 2023)
The aim of this paper is to analyze the relationship between gender, age, education, and thermal satisfaction of employees and users in public buildings, such as schools, public administration, and clinics. The study uses data collected from a randomized stratified sample from Bosnia and Herzegovina. The primary variable of interest is a dummy variable indicating whether individuals are satisfied with the heating of the rooms. Our results revealed that gender and education level might be significant factors. However, when controlling for the type of object, the observed differences were no longer present. Furthermore, our findings show that the results do not differ significantly when the dependent satisfaction variable is measured as binary (dummy) or on a five-point Likert scale. Logistic regression provides an intuitive interpretation in terms of odds. Our study also indicates that age may be a critical predictor in the evaluation of indoor temperature, with older participants reporting the rooms in institutions to be warmer than the younger ones. The outcomes of this research could be valuable in developing policies aimed at improving energy efficiency of buildings. Understanding optimal thermal satisfaction could have significant implications for thermal energy consumption, particularly in the context of how individual characteristics, such as gender, age, and education level, might contribute to the reduction of energy consumption. By addressing the demand side of the energy consumption equilibrium, we might contribute to the better use of existing energy sources. The findings of this paper could also offer useful guidelines when designing more complex studies, especially regarding the debate if the use of a Likert scale is appropriate.
Keywords: D1; 330; thermal satisfaction; age; gender; education level; Bosnia and Herzegovina